Investigating the modulation of stimulus types on language switching costs: Do semantic and repetition priming effect matter? - Shen, Qinfang; Chen, Yixin (Frontiers in Psychology, 2023)
In the present study, I investigated the influence of stimulus types on bilingual control in the language switching process. The commonly employed stimuli in language switching studies – Arabic digits and objects – were compared to further investigate the way in which inhibitory control could be modulated by semantic and repetition priming effects. The digit stimuli have two unique characteristics in the language switching paradigm, for example, they are present repeatedly and are semantically related to each other, compared with pictural stimuli. Thus, these unique characteristics might influence the operation of inhibitory control in bilingual language production, modulating the size and asymmetry of switching costs. To this end, two picture control sets were set up to match those characteristics: (1) a semantic control set, in which picture stimuli belong to the same category group, such as, animals, occupations or transportation and specific semantic categories were presented in a blocked condition; and (2) a repeated control set, in which nine different picture stimuli were repeatedly presented. When comparing the digit condition and the standard picture condition, analyses of naming latencies and accuracy rates revealed that switching costs were reliably smaller for digit naming than for picture naming and the L1 elicited more switching costs for picture naming than for digit naming. On the other hand, when comparing the digit condition and the two picture control sets, it was found that the magnitude of switching costs became identical and the asymmetry in switching costs became much smaller between the two languages. These patterns of data clearly point to the influence of semantic and repetition priming effects on the inhibitory control processes in bilingual language production. Specifically, the fact that the magnitude of switching costs became smaller in the two picture control groups reflects a reduction in the global inhibition of the non-target language or that the inhibitory control is less required, which resulted from the repetition and semantic priming effects formed in the two picture control sets. Furthermore, it is suggested that the local inhibitory control in the semantic control block might also modulate the switching costs.